MEMBANGUN BUDAYA MASYARAKAT PEDESAAN DENGAN TEKNOLOGI INFORMASI TANTANGAN CITIZEN GLOBAL DI DESA AIR ITAM KECAMATAN PENUKAL KABUPATEN PENUKAL ABAB LEMATANG ILIR - Mutrilgandi, Mutrilgandi (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2018)
The culture of society is a legacy of society before the need for its preservation by the next generation. The development of information technology is of course a shift in cultural values from the influence of technology development. It needs to develop the culture of rural communities so that culture continues to develop in the era of technology with the emergence of global citizen. In this study the method used is qualitative research. Data collection techniques are interview, observation and documentation. Interview conducted on the respondents according to the researcher can represent the water village community, then the researcher also conducted observation on the research object that is the water village community, PALI regency, south sumatera province.Respondents who researcher 1) community leaders 2) village tools 3) community 4 ) teenagers, from this study expect the culture of rural communities can be developed through the use of technology and maintaining imformation in the era of global citizen. In maintaining the culture of rural communities in the era of technology is done by 1) at rural about information technology 2) forming cultural group of rural community 3) conducting guidance to young generation in order to preserve local culture. Keywords—  Local culture, technological development, towards global citizen